Book review: Extreme hydrology and climate variability, monitoring, modelling, adaptation and mitigation, by A. Melesse, W. Abtew & G. Senay (Eds.), 2019. Elsevier Inc., Amsterdam. 580 pages. Paperback: price $170.00, ISBN 9780128159989 - Graf, Renata (Geologos, 2020)
Book review: Extreme hydrology and climate variability, monitoring, modelling, adaptation and mitigation, by A. Melesse, W. Abtew & G. Senay (Eds.), 2019. Elsevier Inc., Amsterdam. 580 pages. Paperback: price $170.00, ISBN 9780128159989